2022
DOI: 10.1021/acsami.2c05424
|View full text |Cite
|
Sign up to set email alerts
|

Composite Indium Tin Oxide Nanofibers with Embedded Hematite Nanoparticles for Photoelectrochemical Water Splitting

Abstract: Hematite is a classical photoanode material for photoelectrochemical water splitting due to its stability, performance, and low cost. However, the effect of particle size is still a question due to the charge transfer to the electrodes. In this work, we addressed this subject by the fabrication of a photoelectrode with hematite nanoparticles embedded in close contact with the electrode substrate. The nanoparticles were synthesized by a solvothermal method and colloidal stabilization with charged hydroxide mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Many studies have shown that doping NPs or ions into NFs can effectively improve their electrical conductivity, catalytic activity, mechanical stability, photoelectrochemical performance, etc [12,128,258,259]. Sanger et al doped Al in zinc oxide hollow NFs to effectively improve the sensitivity of gas sensors [260].…”
Section: Othersmentioning
confidence: 99%
“…Many studies have shown that doping NPs or ions into NFs can effectively improve their electrical conductivity, catalytic activity, mechanical stability, photoelectrochemical performance, etc [12,128,258,259]. Sanger et al doped Al in zinc oxide hollow NFs to effectively improve the sensitivity of gas sensors [260].…”
Section: Othersmentioning
confidence: 99%
“…Today, with the rapid development of the global economy, environmental pollution and energy shortages need to be urgently addressed. Hydrogen is a clean and efficient renewable energy source, and among numerous hydrogen production methods, photoelectrochemical (PEC) water splitting can efficiently produce hydrogen from abundant sunlight. Since TiO 2 was initially reported as a photoelectrode for water splitting, numerous light-absorbing semiconductor materials, such as ZnO, g-C 3 N 4 , CdS, and BiVO 4 , have been employed in PEC water splitting. Nevertheless, almost none of them are well qualified for a satisfactory light response range, environmental and human friendliness, or high corrosion resistance simultaneously.…”
Section: Introductionmentioning
confidence: 99%